Impact of Medical Technologist’s Working Environment on Health Problems: Using Data from the 6th Korean National Health and Nutrition Examination Survey - Taewon JUNG; Miran LEE; Sang-ha KIM; Sunghyun KIM; Young-Kwon KIM (Korean Journal of Clinical Laboratory Science)
This study analyzed the correlation between the working environment and health issues among medical technologists. Two hundred and fifty medical technologists were selected for the research based on the data collected from the 6th Korean Working Conditions Survey (KWCS) conducted from October 2020 to April 2021. The findings showed that 51.6% of the respondents reported one or more health problems, with fatigue and musculoskeletal issues being the most prevalent. The analysis suggested that psychosocial risk factors had the greatest impact on health problems. By contrast, medical technologists with non-regular employment and lower incomes were more likely to experience sleep disorders and mental health issues. Differences in health problems were also observed according to age, education level, and work location, whereas no significant differences were found concerning sex. Policy interventions are needed to improve the health of medical technologists, and ongoing research into the relationship between the working environment and health outcomes is recommended.